Pathological and Topographical Classification of Craniopharyngiomas: A Literature Review - James Lubuulwa; Ting Lei (Journal of Neurological Surgery Reports, 2016)
Abstract Craniopharyngiomas (CPs) are clinically relevant tumors of the sellar region and are associated with high morbidity and occasional mortality. There are two different subtypes of CPs that differ clinically and pathologically: adamantinomatous CP and papillary CP. The differential diagnosis is still challenging even with developments in preoperative imaging as several tumors of the sellar/parasellar region share a continuum of clinical characteristics and imaging similarities. Several topographical classifications of CPs have been mentioned in literature, but to date, there has not been a consensus on a standard reference classification system and there is need to a develop such a model.